2019
DOI: 10.1002/cam4.2626
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy treatments, costs of care, and survival for patients diagnosed with small cell lung cancer: A SEER‐Medicare study

Abstract: Objectives The effectiveness and costs of new treatments should be assessed in relation to existing practice. We describe treatments, survival and costs for advanced or metastatic small cell lung cancer (SCLC) patients receiving systemic therapy in the period preceding the introduction of immunotherapies. Materials and Methods This was a retrospective cohort study of patients aged ≥65 years, identified using linked Surveillance, Epidemiology, and End Results and Medicare databases. Individuals with a new prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The PFS and OS in patients with CR or PR after induction chemotherapy were 7.2 months and 12.9 months compared to 5.3 months and 10.9 months in patients with SD, respectively. Standard of first-line treatment with platinum-based chemotherapy for extensive-stage SCLC, a median OS was in range of 9 to 11 months, 20,21 which was the same in our study.…”
Section: Discussionsupporting
confidence: 82%
“…The PFS and OS in patients with CR or PR after induction chemotherapy were 7.2 months and 12.9 months compared to 5.3 months and 10.9 months in patients with SD, respectively. Standard of first-line treatment with platinum-based chemotherapy for extensive-stage SCLC, a median OS was in range of 9 to 11 months, 20,21 which was the same in our study.…”
Section: Discussionsupporting
confidence: 82%
“…28 Second, there is evidence that the clinically meaningful benefit (such as objective response rate and progression-free survival) of subsequent SACTs decreases as the number of lines of prior SACT increases. [34][35][36][37][38] It is Table 2. The proposed standard dataset (top row) comprises the minimum data to be collected regarding the current disease status (columns 1-4) and anti-cancer therapy (columns 5-9) that would help determine the line of therapy (LoT, column 10).…”
Section: A Proposed Systematic and Comprehensive Framework To Determine Lot Terminology And Definitionsmentioning
confidence: 99%
“…20 Two population-based studies conducted in Canada and the US described chemotherapy use in patients diagnosed with SCLC but did not stratify their results by age. 22,23 A recent review of real-world evidence of treatment patterns and outcomes reported that these had remained poor over the preceding 20 years but they did not present their results by age. 24 Our results should be interpreted considering contemporary practice.…”
Section: Noteci: Confidence Intervalmentioning
confidence: 99%